Motivational strategies used by health care professionals in stroke survivors in rehabilitation: a scoping review of experimental studies - Fernandes, Júlio Belo; Fernandes, Sónia; Domingos, Josefa; Castro, Cidália; Romão, Ana; Graúdo, Susana; Rosa, Gonçalo; Franco, Tânia; Ferreira, Ana Patrícia; Chambino, Claudine; Ferreira, Bruno; Courela, Susana; et al. (Frontiers in Medicine, 2024)
Cognitive and motor impairments are common among stroke survivors. Physical therapy is often used to improve the functional capacity of stroke survivors. However, limited adherence to rehabilitation programs is a challenge. Motivation plays a crucial role in the success of rehabilitation programs as it influences individual adherence to treatment and overall health outcomes. This review aims to identify current trends in motivational strategies used by healthcare professionals for stroke survivor rehabilitation. Following the framework developed by Arksey and O'Malley, a scoping review was conducted. We performed a literature search using MEDLINE, CINAHL, the Cochrane Central Register of Controlled Trials, Nursing & Allied Health, and MedicLatina databases. A total of 906 papers were identified. After selecting and analyzing the articles, 17 papers were included in this review. Health professionals use various strategies to motivate stroke survivors. These approaches include establishing a therapeutic alliance, improving patients' health literacy, defining realistic goals, fostering problem-solving skills, personalizing the rehabilitation program, showcasing success stories, utilizing persuasive techniques, offering encouragement and compliments, providing emotional support, and effectively managing symptoms. The knowledge gathered in this review can guide healthcare professionals in helping patients overcome barriers to rehabilitation, improve their motivation, and ultimately enhance their recovery outcomes.